Strategiczne podejście w organizacji procesów innowacyjnych - Szatrowa, J.W. (Strategic approach to innovation processes in an organization, 2006)
The paper describes the innovation strategy as the key functional strategy in the contemporary development conditions. The condition of innovative success is a strategic, long-term and complex approach. It is necessary to incorporate the innovation strategy into the general business strategy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 307-309